2000
DOI: 10.1029/2000jd900110
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of covariance with application to atmospheric time series

Abstract: Abstract.Multiscale analysis of univariate time series has appeared in the literature at an ever increasing rate. Here we introduce the multiscale analysis of covariance between two time series using the discrete wavelet transform. The wavelet covariance and wavelet correlation are defined and applied to this problem as an alternative to traditional cross-spectrum analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
249
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(255 citation statements)
references
References 36 publications
5
249
0
1
Order By: Relevance
“…Note that the WCC is roughly analogous to its Fourier counterpart, the magnitude squared coherence, but the WCC is related to bands of scales (frequencies) [32]. The WCC ρ XY,τ λ j ∈ [−1, 1], and is used to determine lead/lag relationships between two time series on different scales λ j .…”
Section: The Wavelet Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the WCC is roughly analogous to its Fourier counterpart, the magnitude squared coherence, but the WCC is related to bands of scales (frequencies) [32]. The WCC ρ XY,τ λ j ∈ [−1, 1], and is used to determine lead/lag relationships between two time series on different scales λ j .…”
Section: The Wavelet Methodologymentioning
confidence: 99%
“…The WCC ρ XY,τ λ j ∈ [−1, 1], and is used to determine lead/lag relationships between two time series on different scales λ j . The confidence interval for the WCC is based on an extension of the classical result on the Fisher's Z-transformation of the correlation coefficient [32]. Thus, an approximate 100(1−2p)% confidence interval for the WCC is given by tanh{h…”
Section: The Wavelet Methodologymentioning
confidence: 99%
“…The periods for the calibration (1 October 1997 to 30 September 2001) and for the prediction (1 October 2001 to 31 August 2002) were the same as for the simple state-space model without decomposition. Previous analysis of the wavelet covariance between the observed and simulated data (see Whitcher et al [2000] for more details), have indicated that a maximum of five different levels is sufficient for these kind of data to capture the relevant error features. This method will be called MODWT-hindcast.…”
Section: Wavelet Transformation and Autocorrelation Shell Representationmentioning
confidence: 99%
“…Wavelet cross spectral analysis using the CWT has been applied to applications such as climatology (Maraun and Kurths (2004), Grinsted et al (2004)) and neuroscience (Lachaux et al, 2002). Wavelet cross-covariance and correlation has also been defined based on the maximal overlap discrete wavelet transform (MODWT) (see Whitcher et al (2000) and Serroukh and Walden (2000)). Their formulation assumes that the d'th order backwards differences of the series can be modelled as a stationary process.…”
Section: Introductionmentioning
confidence: 99%